Delayed Re-epithelialization After Epithelium-Off Crosslinking: Predictors and Impact on Keratoconus Progression - Bonzano, Chiara; Cutolo, Carlo Alberto; Musetti, Donatella; Di Mola, Ilaria; Pizzorno, Chiara; Scotto, Riccardo; Traverso, Carlo Enrico (Frontiers in Medicine, 2021)
PURPOSE: To investigate the demographic and corneal factors associated with the occurrence of delayed re-epithelialization (DRE) after epithelium-off CXL (epi-off CXL). DESIGN: Retrospective case series. METHODS: A chart review was performed to identify patients treated with epi-off CXL. DRE was defined as a corneal epithelial defect, detected by fluorescein staining, that persisted more than 10 days. Slit-lamp examination, anterior segment optical coherence tomography, corneal topography and, corneal in-vivo confocal microscopy (IVCM) were always performed preoperatively and at each follow-up visit (1, 3, 6, 12 months). Logistic regression was used to assess the baseline factors associated with DRE. RESULTS: Data from 153 eyes were analyzed. The mean patients’ age was 24.9±8.5 years, and 47 (30.7%) were females. The average re-epithelization time was 4.7 ± 1.8 days. Six eyes (3.9%) experienced DRE. In the multivariate logistic model, both the patient’s age (OR=1.30, 95% CI 1.1 to 1.6; p=0.019) and the corneal steepest meridian (OR=0.44, 95% CI 0.19 to 0.99, p=0.046) were associated with DRE. Male gender was associated with a slower early nerve regrowth (1 to 6 months) (p=0.048) but not with the occurrence of DRE (p=0.271). Preoperative central corneal thickness was not related with DRE (p=0.066). DRE was not associated with KC progression after epi-off CXL (p=0.520). CONCLUSIONS: The association between DRE and age may reflect the age-related decrease in the corneal healing response. Gender seems to affect re-innervation measured by IVCM but not the re-epithelization time. DRE does not seem to affect the efficacy of epi-off CXL.